Selenium status and its relationship with cardiovascular risk factors in two portuguese populations of S. Miguel Island: Azores Archipelago - Viegas-Crespo, Ana Maria (1998)
Seleniurn forms part of the active site of glutathione peroxidase enzymes which preveut lipid peroxidation in mammals and take pah in tlie direct protection of endothelial cells against reactive oxiygen species that have been implicated in atherogenesis; moreover these enzymes are involved in the biosynthesis of arachidonic acid derivatives platelets and in the regulation of lipoprotein cholesterol metabolisrn (1-4). To provide further insight into the possible role of selenium in cardiovascular disease, we investigated the assotiation between selenium status and generally accepted cardiovascular risk factors in two populations living in rural and fishing comrnunities of Rabo de Peixe - S. Miguel Island ofthe Azores Archipelago. (Introduction)